Effect of Maytenus macrocarpa“Chuchuhuasi” in the male system reproductive of mouse (Mus musculus) - Acosta, Láyonal G. (2013)
Maytenus macrocarpa(chuchuhuasi) is native tree of the Peruvian Amazon used as traditional medicine for the treatment of many diseases, but its effect on the male reproductive system has not yet been elucidated. The aim of this study is evaluate the effect of aqueous extract of M. macrocarpa in daily doses for 7 days on reproductive parameters of male mice. We used C57BL mature male mice divided into 2 groups (n= 10), Control Group (C): 0.9% NaCl and Treatment group (T): Aqueous extract of Chuchuhuasi, both supplied daily via oral gavages. At the eight day of treatment the mice were euthanized. The weight of the body and reproductive organs: testis, epididymis and vas deferens, were registered. Concentration, motility and sperm morphology were evaluated. The results showed significantly differences (t- Student test P<0.05) in the weight of the head and body epididymis (C: 19.25±1.1 vs T: 21.26±2.0), vas deferens (C: 10.61±0.7 vs T: 11.75±0.5), progressive sperm motility (C: 42.16±5.2 vs T: 25.82±8.4) and immobile sperm (C: 36.05±4.9 vs T: 48.51±7.2). No difference in sperm count was observed. The sperm normal morphology diminished with ingest of M. macrocarpa(tStudent test p <0.05) (C: 39.72±1.3 vs T: 30.78±4.9). We conclude that the aqueous extract of chuchuhuasi, has a negative effect on the male reproductive system of mice.